Effect of Heat-Labile Factors on the Neutralization of Vaccinia Virus by Human Sera - Takabayashi, Kazuaki (1973)
The effect of unheated guinea pig and human prevaccination serum on the neutralization of vaccinia virus was studied. Enhancement of neutralization was found in all sera containing antibody and was more marked (20- to 150-fold) in sera obtained in the first weeks after primary vaccination than in sera from immune adults or cord sera (4- to 25-fold). The enhancing factor was thought to be complement because it was destroyed by heating and ethylenediaminetetraacetic acid treatment. The fresh serum-enhanced neutralization test represents a highly sensitive and specific test which can be applied to measure low levels of vaccinia antibody not detectable by other means.